Some relationship between students’ creative and intellectual abilities - Karkockienė, Daiva; Butkienė, Giedrë (Psichologija, 2005)
The aim of this study was to reveal some interactions between creative and intellectual abilities as well as interactions of creative abilities variation after training of creativity and intellectual abilities. Creativity in this study is understood in terms of cognitive abilities of creative thinking expressed by divergent thinking components as fluency, flexibility and originality (Guilford, 1950; Torrance, 1974; Sternberg and O’Hara, 1999). Divergent thinking is the one component of creative thought understood as the distinct capacity to generate multiple alternative solutions as opposed the one correct solution. Divergent thinking is assessed through open-ended tests such as consequences and alternative uses, where responses are scored for fluency (number of responses), flexibility (category shifts in responses) and originality (uniqueness of response). There were 160 students (mean age 23) from Vilnius Pedagogical University. E. P. Torrance test (verbal, form A, 1974) was used to identify cognitive abilities of creative thinking (fluency, flexibility and originality). R. Amthauer test (IST-70) was used to measure intellectual capabilities. The subjects were randomly assigned to two experimental (n = 80) and control groups (n = 80). The experimental group took part in creativity training program during four months (32 hours). The special program of creativity training was used once a week for four months (32 hours). The program was made-up for the developing cognitive abilities of creative thinking (fluency, flexibility and originality). Special methods (brain storming, ideas generation, drama, divergent tasks etc.) were used to develop students’ creative abilities. The experimental group took part in creativity training program. The study revealed the interactions between creative abilities evaluated by Torrance test (TTCT, verbal A form) and intellectual abilities evaluated by Amthauer IST. Weak interactions were revealed between flexibility and BE subtest of abstract verbal ability (r = 0,24, p < 0,01), as well as originality and BE subtest of abstract verbal ability (r = 0,22, p < 0,01). There are some weak links between all cognitive parameters of creativity (fluency, flexibility and originality) and the results of Sentence Supplement (SP) subtest (r = 0,17, p < 0,05) as well as between fluency, flexibility and ability to percept language meaning (ŽI) subtest (r = 0,18, p < 0,05; r = 0,16; p < 0,05). No such tendency was found between other creative and intellectual abilities. Though there were no significant interactions between increase of creative abilities and intellectual abilities, clear links were found between originality and abstract verbal ability (BE) and spatial imagination (KU) (r 0, BE = 0,41; r 0, KU = 0,38; r 0,05 = 0,53).